2021
DOI: 10.1371/journal.pone.0251768
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chest CT body composition parameters on clinical outcomes in COVID-19 patients

Abstract: We assessed the impact of chest CT body composition parameters on outcomes and disease severity at hospital presentation of COVID-19 patients, focusing also on the possible mediation of body composition in the relationship between age and death in these patients. Chest CT scans performed at hospital presentation by consecutive COVID-19 patients (02/27/2020-03/13/2020) were retrospectively reviewed to obtain pectoralis muscle density and total, visceral, and intermuscular adipose tissue areas (TAT, VAT, IMAT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 43 publications
1
50
0
2
Order By: Relevance
“…Although not optimal, other landmarks and isolated muscle groups have been used in clinical settings, including pectoralis muscle area, psoas muscle area or thigh muscles [11,12]. Low muscle mass is associated with clinical outcomes in COVID-19 patients; according to Besutti et al, higher pectoralis muscle crosssectional area, measured by chest CT images, showed a protective effect on hospitalization, mechanical ventilation (MV) and death [13]. Similar findings were reported by Ufuk et al using chest images for pectoralis SMI assessment in 130 patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although not optimal, other landmarks and isolated muscle groups have been used in clinical settings, including pectoralis muscle area, psoas muscle area or thigh muscles [11,12]. Low muscle mass is associated with clinical outcomes in COVID-19 patients; according to Besutti et al, higher pectoralis muscle crosssectional area, measured by chest CT images, showed a protective effect on hospitalization, mechanical ventilation (MV) and death [13]. Similar findings were reported by Ufuk et al using chest images for pectoralis SMI assessment in 130 patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the sample by Kim et al, the ICU admission rate was only 8.3% (35). The percentage of patients receiving mechanical ventilation were 6.6%, 11.5% (22,26,35). The study by Moctezuma-Velázquez had a patient cohort with characteristics closer to ours, with an ICU admission rate of 40% and a mortality of 25%, revealing no association with clinical outcomes (27).…”
Section: Discussionmentioning
confidence: 52%
“…Some authors have described that certain body composition parameters can identify unfavorable outcome in patients with Covid-19. For example, a higher level of adipose tissue has been associated with higher rates of hospitalization and mechanical ventilation (22)(23)(24). In another study, higher visceral fat area and higher abdominal circumference measured at the lumbar level were correlated with higher rates of transfer to the Intensive Care Unit (ICU) and mechanical ventilation, but mortality was not investigated (25).…”
mentioning
confidence: 99%
“…There has been recent work in developing deep learning based segmentation methods that also can be incorporated in such analysis [25] , [26] . In a recently published study, measure of muscle and visceral adiposity on chest CT at T7-T8 level was also associated with risk of hospitalization, mechanical ventilation and death [27] . In the future, we plan to develop a model that includes various measures of muscle adiposity and visceral adiposity on chest CT in addition to abdominopelvic CT to predict the need for hospitalization in patients that have chest CT but not abdominopelvic CT.…”
Section: Discussionmentioning
confidence: 96%